Developmental stages of Trypanosoma cruzi-like flagellates in Cavernicola pilosa - Marinkelle, C. J. (Revista de Biología Tropical, 1982)
The developmental stages of Trypanosoma cruzi ssp., found in the intestinal tract of Cavernicola pilosa, are described and measurements given for nine life stages. The frequencies of the various stages in foregut, midgut and hindgut of the triatomines are provided; parasites were rare in the foregut and metatrypomastigotes were seen only in the mid- and hindguts. AH adult bugs examined harboured intestinal infections of T. cruzi-like flagellates, large clumps of amastigotes were frequently observed in the midgut. The faeces of C. pilosa, containing metacyclic trypomasiigotes, did not produce patent parasitaemia when inoculated into mice. Inoculated mice were not protected against subsequent challenge infections with the highly virulent Tulahuen stock of T. c. cruzi. The blood of bats also failed to produce parasitaemia when inoculated into mice, nor were the mice protected against subsequent challenges with T. c. cruzi. Although the developmental stages described were very similar to those of T. c. cruzi it is presumed that they were stages of T. c. marinkellei because of their failure to infect mice and Rhodnius prolixus, and their failure to protect inoculated mice against challenge with T. c. cruzi.